Effect of ethanol leaf extract of Plukenetia volubilis on blood glucose and triglyceride levels of mice induced by alloxan - Dewi Handayani; Zahra Salsabila; Hermansyah Amir; Nurhamidah Nurhamidah; Sura Menda Ginting (Jurnal Pendidikan Kimia (JPKIM), 2023)
The study aims to determine the phytochemical profile of ethanol extract of kacang saca leaves and its effect on reducing blood glucose and triglyceride levels. Used 18 mice were divided into six groups, namely the normal group, the positive control group (glibenclamide treatment), the negative (alloxan induction), and the treatment group doses used were 0.0262 mg/dL, 0.0525 mg/dL, and 0.105. mg/dL. The treatment of mice was carried out for 10 days with three measurements, namely before treatment, on the 7th day, and on the 10th day of giving the extract. Phytochemical test results showed the presence of flavonoid compounds, alkaloids, steroids, saponins, and tannins. The data obtained were analyzed using the SPSS application. The results of the measurement of blood glucose levels in mice on the 7th day showed normal numbers, the results of data analysis showed no significant difference, namely 0.164. In the measurement of triglycerides, triglyceride levels fell in two groups, namely groups 1 and 3. Data on the 10th day there was an increase in blood glucose and triglycerides. Analysis of the data showed that there was no significant difference in each group on day 7 and day 10. The ethanol extract of cacao beans has the potential to reduce glucose levels used for 7 days but does not affect the triglyceride levels of mice.Keywords: Alloxan; Glucose; Mice; Triglyceride; Plukenetia volubilis